THE EPENDYMAL ROUTE FOR INSULIN-LIKE GROWTH FACTOR-1 GENE THERAPY IN THE BRAIN - Hereñú, Claudia B. (2009)
Intracerebroventricular administration of the peptide insulin-like growth factor-1 (IGF-1) has been shown to be an effective neuroprotective strategy in the brain of different animal models, a major advantage being the achievement of high concentrations of IGF-1 in the brain without altering serum levels of the peptide. In order to exploit this therapeutic approach further, we used high performance recombinant adenoviral (RAd) vectors expressing their transgene under the control of the potent mouse cytomegalovirus immediate early (mCMV) promoter, to transduce brain ependymal cells with high efficiency and to achieve effective release of transgenic IGF-1 into the cerebrospinal fluid (CSF). We constructed RAd vectors expressing either the chimeric protein (TK/GFP)(fus) (green fluorescent protein fused to HSV1 thymidine kinase) or the cDNA encoding rat IGF-1, both driven by the mCMV promoter. The vectors were injected into the lateral ventricles of young rats and chimeric GFP expression in brain sections was assessed by fluorescence microscopy. The ependymal cell marker vimentin was detected by immunofluorescence and nuclei were labeled with the DNA dye DAPI. Blood and CSF samples were drawn at different times post vector injection. In all cerebral ventricles, vimentin immunoreactive cells of the ependyma were predominantly transduced by RAd-(TK/GFP)(fus), showing nuclear and cytoplasmic expression of the transgene. For tanycytes (TK/GFP)(fus) expression was evident in their cytoplasmic processes as they penetrated deep into the hypothalamic parenchyma. Intracerebroventricular injection of RAd-IGF-1 induced high levels of IGF-1 in the CSF but not in serum. We conclude that the ependymal route constitutes an effective approach for implementing experimental IGF-1 gene therapy in the brain.